Granular cell differentiation: A review of the published work. Issue 3 (March 2017) - Cardis, Michael A.; Ni, Jonathan; Bhawan, Jag
Abstract: Since the initial description of the granular cell tumor in 1926, numerous other neoplasms, both benign and malignant, have been described to exhibit granular cell change. In most cases, diagnosis remains straightforward via recognition of retained histopathological morphology of the archetypal tumor, despite the presence of focal granular appearance. However, tumors with granular cell differentiation can present a diagnostic challenge either by mimicking alternative diagnoses, or by failing to exhibit architectural clues of the primary entity, thus requiring an immunohistochemical work‐up. In light of this, it is important to be aware of the various entities that have been reported to exhibit granular cell morphology. In this review such tumors are discussed along with pertinent clinical and histopathological features.